Characterization of risk management practices among strawberry growers in the southeastern United States and the factors associated with implementation. (April 2021) - Yeargin, Thomas A.; Fraser, Angela M.; Gibson, Kristen E.
Abstract: Strawberries, the fifth most preferred fresh fruit in the United Sates, are one of several fresh produce commodities in the U.S. linked to outbreaks of foodborne disease. However, the industry is not well characterized. Additionally, in the southeastern U.S. (SEUS), very small strawberry-growing operations are particularly common, presenting unique challenges to implementation of risk management practices (RMP). A 45-item survey was developed to collect data regarding each strawberry grower's location, farm characteristics, and RMP. The majority of SEUS growers in this study harvested strawberries on less than 5 acres with 2.00–4.99 acres being most common (41%) and reported a revenue based on strawberry production of US25, 001–250, 000 (63%). Implementation of a pre-harvest policy and animal intrusion monitoring were both highly prevalent whereas testing of pre-harvest agricultural water was least common. Growers also reported using RMP but were less likely to document them. For example, 76.6% of growers reported their employees had attended food safety training; meanwhile, only 38.9% had documented training. The frequency of use and documentation of RMP were also found to be impacted by certain farm characteristics, most notably acreage, revenue, presence of third-party audit, and presence of a written food safety plan. Based on these results, strawberry growers, particularly in the SEUS, may benefit from additional education tailored to align with farm scale that includes instruction on documentation. Highlights: The southeastern U.S. strawberry industry is not well characterized. A majority of grower respondents harvested strawberries on less than 5 acres. Frequency of use and documentation of RMP are impacted by farm scale. Strawberry growers may benefit from education tailored to farm scale.